Five Vital Components in an Occupational Therapy-Based Municipal Weight Loss Program Obtained Through Research Circles - Jessen-Winge, Christina; Lee, Kim; Surrow, Signe; Christensen, Jeanette R. (Frontiers in Rehabilitation Sciences, 2022)
Introduction: Currently 1.9 billion adults worldwide are estimated to be overweight or obese. Weight loss sustainability is difficult, and weight loss rehabilitation programs have been criticised for having an individualistic approach. It has been suggested that occupational therapists could be used as part of a transdisciplinary approach because of their holistic perspective. During the development of an occupational therapy- based weight loss program five components arose as essential from earlier interviews with health professionals and citizens with obesity: diet, physical activities, social relations, habits and balancing everyday life. Before developing the program, we needed a clearer picture of which strategies should support the five components. The aim of this study was to obtain a description of strategies related to the five components that could support weight loss to become part of everyday life of people with obesity. Methods: This study took a participatory design by using research circle (RC) methodology. Two RC groups were created, one with occupational therapists and one with citizens with obesity. Researchers participated in both RC groups. Data was obtained through democratic principles. The two RC groups met four times over a period of four months. Qualitative content analysis was conducted. Results: Five themes arose: 1) Diet – Find the line between either-or, 2) Physical activity – Break the comfort zone, 3) Social relations - Stand strong together, 4) Habits – Focus on possibilities instead of bad habits, and 5) Balancing everyday life – Handling life´s bumps. Conclusion: The strategies for a weight loss program including the five components should include awareness of senses and activity patterns surrounding meals, taking one step at a time when focusing of physical activities and be conscious of values, include family and friends in the program to find common ground and self-confidence and use re-placement activities. We suggest that the component of balancing everyday life should be seen as an overall component as all strategies are related to finding meaning and variation in activities which is part of an ongoing weight loss process.